2013
DOI: 10.2807/ese.18.09.20408-en
|View full text |Cite
|
Sign up to set email alerts
|

A Clostridium perfringens outbreak traced to temperature-abused beef stew, Norway, 2012

Abstract: On 21 January 2012, the Norwegian Food Safety Authority was informed about gastrointestinal illness among 111 swimming club members, who were staying at a hotel in Trondheim. A hotel dinner on 20 January was their only common meal. Kitchen staff were interviewed, and food leftovers and kitchen environment were sampled. A case was defined as a swimming team member staying at the hotel from 20 to 22 January, who fell ill with diarrhoea, abdominal pain or nausea during this period. A total of 43 cases were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Most cases of C. perfringens outbreaks in humans are associated with the incorrect temperature of cooked food. C. perfringens spores can persist in cooked food and germinate during the cooling down and storage of prepared foods [ 162 ]. Due to the rapid proliferation of C. perfringens (doubling time less than 10 min) and the wide temperature range at which they can grow, C. perfringens can reach levels that cause food poisoning faster than any other foodborne pathogen [ 163 ].…”
Section: Zoonosismentioning
confidence: 99%
“…Most cases of C. perfringens outbreaks in humans are associated with the incorrect temperature of cooked food. C. perfringens spores can persist in cooked food and germinate during the cooling down and storage of prepared foods [ 162 ]. Due to the rapid proliferation of C. perfringens (doubling time less than 10 min) and the wide temperature range at which they can grow, C. perfringens can reach levels that cause food poisoning faster than any other foodborne pathogen [ 163 ].…”
Section: Zoonosismentioning
confidence: 99%
“…There was no evidence of outbreaks of C. perfringens and C. botulinum linked to persistence. Some studies describe C. perfringens outbreaks related to episodes occurring after consumption of improperly reheated meat products in restaurants (Mellou et al, 2019;Wahl et al, 2013) and a catered lunch (Rinsky et al, 2016). There are limited published studies tracing these clostridial species in meat processing or identifying persistent contamination; although Jiang et al (2022) demonstrated distribution of the same pulsotype across the FoPE and associated meat samples of beef slaughterhouses on single sampling occasions, persistent contamination of the FoPE over time was not identified.…”
Section: Pathogens Able To Persist In the Processing Environment Of T...mentioning
confidence: 99%